Trade and Economic Cooperation Between Ukraine and the Republic of Belarus: Historical Discourse (1991–2020) - Alexiyevets, Lesya (Український історичний журнал, 2021)
The aim of the research is to study trade and economic cooperation between Ukraine and the Republic of Belarus, the agreement and legal basis of bilateral cooperation, the dynamics of foreign trade turnover, tendencies and forms of production cooperation in the context of modern challenges. The methodology of work is a complex of scientific principles, general scientific and special historical methods, as well as interdisciplinary and comprehensive approaches to the historical discourse of modern Ukrainian-Belarusian trade and economic relations based on the integral use of sources on this issue. The scientific novelty is stipulated by insufficient research of trade and economic aspects of cooperation between Ukraine and the Republic of Belarus in the Ukrainian historiography at the present stage, where, with few exceptions, there are almost no generalized papers on these issues. The author’s view on the dynamics of cooperation between the two countries for the whole period of 1991–2020 is shown, the peculiarities of bilateral cooperation after the presidential elections on August 9, 2020 in Belarus, which led to deepening political crisis in the republic, have been clarified, the prospects of given research have been determined. The conclusions. It has been proven that almost thirty years of experience of cooperation between Ukraine and the Republic of Belarus in the new geopolitical realities is the evidence of the importance of bilateral trade and economic cooperation based on pragmatism and mutual interest, broad contacts at the level of the heads of the states, governmental and non-governmental structures, diplomatic bodies as well agreement and legal basis. It has been shown that owing to the industrial cooperation of the two states, the growth of the dynamics of mutual trade turnover, the search for constructive solutions in interregional cooperation, the concerted work of all structures coordinating Ukrainian-Belarusian relations, the accumulated institutional and legal support, it became possible to preserve the accumulated potential in the interstate relations ensuring the vector of bilateral opportunities in the context of integration and globalization processes of the present time. At the same time, in connection with the ongoing political crisis in Belarus, the format of bilateral relations has changed. Although economic cooperation continues, the challenges affecting the mutual dialogue are inducing Kyiv to consider different options for the development of bilateral cooperation; in the economic dimension, the search for opportunities to diversify and replace the Belarusian products is taking place.